2021
DOI: 10.1002/csc2.20572
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient uptake behavior of peanut under optimum fertilization management in China

Abstract: Balanced fertilization is one of the most critical management factors for attaining high yields. Assessing pod yield and plant nutrient demand can provide theoretical guidance for fertilization management of high yielding peanut (Arachis hypogaea L.). Following this rationale, a large dataset was collected from field experiments (n = 313) across the main peanut planting regions of China for a period spanning from 2000 to 2019 to evaluate nutrient uptake behavior of peanut under current optimum fertilization ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Compared with other studies with large sample sizes, the N requirement to produce 1000 pods in this study was similar to the result of 42.2 kg [ 25 ], but slightly lower than in other studies [ 31 , 32 ]; P and K demand was lower than what was estimated across China [ 31 ] and in the same region of central north China [ 32 ]. Estimation variation in nutrient requirement may be related to differences in planting regions, cultivars, soil conditions, yield level, and tillage [ 30 , 33 ].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Compared with other studies with large sample sizes, the N requirement to produce 1000 pods in this study was similar to the result of 42.2 kg [ 25 ], but slightly lower than in other studies [ 31 , 32 ]; P and K demand was lower than what was estimated across China [ 31 ] and in the same region of central north China [ 32 ]. Estimation variation in nutrient requirement may be related to differences in planting regions, cultivars, soil conditions, yield level, and tillage [ 30 , 33 ].…”
Section: Discussionsupporting
confidence: 82%
“…Estimation variation in nutrient requirement may be related to differences in planting regions, cultivars, soil conditions, yield level, and tillage [ 30 , 33 ]. Crucsiol et al [ 3 ] demonstrated that N absorption for older cultivars remains high, while newer cultivars were less demanding in N. Xie et al [ 25 ] found that the values of nutrient requirement simulated by modeling were lower than the average observed values, and they explained that the N, P, and K predicted by the model were the optimal nutrient requirements under the conditions of the balanced absorption of N, P, and K. However, high soil nutrient supply and excessive fertilization practices may have resulted in excess nutrient uptake [ 31 ]. A large number of studies have demonstrated that crop nutrient uptake positively correlates with yield level, but the yield increase decreases when the yield reaches a certain level [ 32 ].…”
Section: Discussionmentioning
confidence: 99%